AB0486 LACK OF CONSISTENT STANDARD OF CARE IN SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS IN REAL WORLD. (June 2019) - Touma, Zahi; Hoskin, Ben; Atkinson, Christian; Bell, David; Massey, Olivia; Lofland, Jennifer H.; Berry, Pam; Karyekar, Chetan; Costenbader, Karen
Abstract : Background: Current guidelines do not necessarily reflect current standard of care (SOC) or treatment patterns in SLE in real world. Objectives: To describe SLE SOC in the EU5 and US and assess need for a more efficient and defined treatment pathway. Methods: A cross-sectional study of 263 rheumatologists in the US and EU5. Data were collected from the Adelphi Real World 2015 Lupus Disease Specific Programme (DSP). Physicians were asked to complete patient record forms (PRFs) for the next 5 patients consulting with SLE; the same patients were asked to complete patient self-completion (PSC) forms describing how SLE affected them. PRFs collected data pertaining to the patient's diagnosis, disease history, current clinical outcomes, treatment and management history. PSCs focused on similar data collection and included patient reported outcome measures (PROs) to assess the humanistic burden. Chi-squared tests were conducted to ascertain significance. Results: Data was extracted from 1376 PRFs, and 591 PSCs. 35.6% of patients were currently on their first line of therapy, 40.0% second line, and third line or more 24.4%. Significant differences were observed between US and EU5 in current treatment classes for first line (p<0.0001) and second line (p=0.0007). Descriptive differences were observed in the third line. In the US monotherapy is used more often first line with antimalarial (AM) (monotherapy EU5 12.5% vs. US 19.3%) and immunosuppressant (IM) (monotherapy EU5 4.6% vs. US 11.1%). Glucocorticoids (GCS) use is higher in the EU5 at 1 st line; both monotherapy (EU5 13.7% vs. US 11.8%) and combination (GCS+AM EU5 28.3% vs. US 16.7%). At second line, IM use (no bio) is higher in EU5 (EU5 64.9% vs. US 56.7%) and biologic use is higher in the US (EU5 5.0% vs. US 8.3%); GCS use is similar (EU5 19.2% vs. US 19.0%). Globally, 84.4% of patients receiving GCS received it continuously with no significant differences observed between markets, EU5 85.5% vs. US 81.9%. A higher proportion of patients in the EU5 have been on GCS for 6 months or longer when compared to the US; EU5 79.9% vs. US 72.5%. Statistically significant differences were seen in the perception of GCS importance between markets (p=0.0004) and concerns with taking GCS (p=0.0140). A higher proportion of patients in the US regarded the use of GCS to at least be very important (very important/essential EU5 65% vs. US 80.6%). A higher proportion of patients in the US were concerned with the use of GCS (somewhat concerned/very concerned EU5 56% vs. US 61.2%). Conclusion: Significant differences in treatment approach between regions highlights the need for a better understanding of this disparity and a united approach to SLE treatment. Despite the high profile of risk factors linked to GCS use in SLE, it continues to be a continuously utilized by a large proportion of SLE patients and there is poor use of flare preventing agents such as antimalarials. Patients and physicians recognize the role of GCS in the management of SLE but also express concerns. Impact of an update to the SLE guidelines and their dissemination with better understanding of risk benefits of GCS vs. immunosuppressive and biologic therapy is warranted. Disclosure of Interests: Zahi Touma Grant/research support from: GSK Canada, Consultant for: UBC, Pfizer, Janssen, Inc, Ben Hoskin Employee of: Adelphi, Christian Atkinson Employee of: Adelphi, David Bell Employee of: Adelphi, Olivia Massey Employee of: Adelphi Real World, Jennifer H. Lofland Employee of: Janssen Global Commercial Strategic Organization, Pam Berry Shareholder of: GSK and Janssen Global Services, Chetan Karyekar Shareholder of: J&J, Employee of: Janssen Scientific Affairs, LLC, Abbott, BMS, Novartis, Karen Costenbader: None declared